Translation in Bahasa Indonesia and Linguistic Validation of Mastectomy Module of BREAST-Q: A Description of The Process - Prajoko, Yan Wisnu; Korwa, Ivani Yunita; Junita, Dila (http://dharmais.co.id/, 2024)
Background: Breast-related Symptom Questionnaire (BREAST-Q) has been globally used and validated to measure the outcomes among women undergoing various breast surgery. There was a lack of tools to evaluate patient’s quality of life and satisfaction after mastectomy in Indonesia. In addition, most patients in Indonesia may feel reluctant to express their honest opinions regarding the post-operative outcome openly. Prior to this issue, this study aims to translate and validate the BREAST-Q Mastectomy Module into Bahasa Indonesia, which can be applied to the Indonesian population. Method: Primarily based on the guidelines from the International Society for Pharmacoeconomics and Outcome Research (ISPOR), the process includes preparation, forward translation, back translation, panel discussion, cognitive debriefing interview with 57 respondents, statistic evaluation of validity and reliability, and final consensus. Results: Two translators worked on two different forward translation, while a third translator handled the back translation. The translations were then discussed and reviewed to reach an agreement on the finalized version. Statistic evaluation showed Pearson’s r value 0.26 in all items, with Cronbach’s alpha range 0.72–0.92 ( 0.70). Bland-Altman plots comparison showed that the direction of the mean difference between score 1 and score 2 is close to zero. At the same time, the limits of agreements exceed the minimally detectable change for both scales, indicating all items are valid, reliable, and reflect the concepts of the BREAST-Q Mastectomy Module. The final version of the Bahasa Indonesia Translation is then approved by the Q-Portfolio team.Conclusion: The translation of BREAST-Q questionnaire Mastectomy Module in Bahasa Indonesia is valid and reliable. It is a suitable instrument to assess the quality of life of patients who underwent mastectomy in the Indonesian population.